AIDS drugs for Africa!' a case study examining transnational AIDS treatment activism and the reduction of global antiretroviral prices from 1996 to 2001 - Kavli, Eleyce M Northcraft (Department of Political Studies, 2014)
Includes abstract. Includes bibliographical references.